Pengaruh Media Sosial terhadap Rekrutmen pada Anggota Kepolisian - Tugimin Supriyadi; Alya Meylinda Putri; Azzahra Rahmita; Bella Aisyah Dinah; Tiara Hasanah Munandar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The National Police of the Republic of Indonesia shall arrange all matters relating to the duties and institutions of the police in accordance with the provisions of the law. Recruitment must be done effectively and efficiently to its vision, mission and goal. Social media plays a strategic role in determining public confidence in governmental organizations/agencies. The recruitment process must be carried out in a creative and innovative way to meet the needs of qualified workforce. The research method used is literature study. The more the State Police of the Republic of Indonesia is involved in the use of social media, the stronger the image of the organization built on the social network, the greater the interest of the candidate members to participate in the organization.